Foreign ownership and firm performance in German services: First evidence based on official statistics - John P. Weche Gelübcke (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2011)
This study provides first comprehensive analyses of foreign-controlled enterprises in the German service sector based on new micro data from official statistics. Various performance measures were examined by comparing unconditional and conditional means and quantile regression techniques were applied. Results reveal persistently superior performance for foreign-controlled affiliates when compared to German-owned affiliates. In contrast, the relationship for profitability is exactly the opposite. Labor productivity becomes insignificant when the comparison group consists of domestically-owned affiliates with a high degree of internationalization. A breakdown by country of origin shows that European affiliates pay lower wages and export less compared to other foreign affiliates and that there is no productivity advantage in favor of US firms like in manufacturing.
Keywords: F15; F21; F23; 330; foreign ownership; firm performance; inward FDI; service sector; multinational enterprise; Dienstleistungssektor; Multinationales Unternehmen; Auslandsniederlassung; Ausländisch; Unternehmensentwicklung; Produktivität; Schätzung; Deutschland